Investigation of the Transfer Capability of the Nigerian 330 kV, 58-bus Power System Network using FACTS Devices (ELEKTRIKA- Journal of Electrical Engineering, 2023)
Over the years, the Nigerian power system is beset with lingering problems, which include severe power losses, as well as very low transfer capability of the transmission network to evacuate power from generating stations to the load at the distribution level. Presently, the Nigerian power industry is undergoing restructuring, especially in the generation and distribution systems. In view of the deregulation of electricity distribution and marketing, the traditional practices of the Nigerian power system are undergoing changes to address the identified problems in the existing power system. Specifically, better utilization of the existing power transmission network to improve on the system transfer capability and minimize cost is one of the key focuses of the deregulation agenda. This work deals with the enhancement of transfer capability of Nigerian 58-bus, 330kV network using FACTS (Flexible Alternating Current Transmission System) devices. FACTS devices are used for controlling transmission voltage, power flow, reducing reactive power losses, and damping of power system oscillations for high power transfer capability. Three FACTS devices; Thyristor Controlled Series Compensator (TCSC), Unified Power Flow Controller (UPFC), and Interline Power Flow Controller (IPFC) were used to investigate the transfer capability of the Nigerian 58-bus power system network. NEPLAN was employed in this work to model the Nigerian 58-bus system and optimally placed the FACTS devices at the weakest buses that were found out through the computation for available transfer capability (ATC) after continuation power flow (CPF) simulation was completed. MATLAB codes were developed and used to calculate power transfer capability of the network without and with FACTS devices. Comparing the three FACTS devices, the results obtained showed that UPFC enhanced the power transfer capability of the network than TCSC and IPFC.